Human‐Induced Downsizing of Animal Communities Weakens Trait Matching Between Tropical Plants and Frugivores - Daniel Guerra; Andressa Cabral; Mariana Paetzolt; Evan Fricke; W. Daniel Kissling; Frederic Lens; Renske E. Onstein (Ecology Letters, 2025)
Defaunation of large‐bodied animals threatens essential ecosystem functions, such as seed dispersal. However, the consequences of this human‐induced downsizing of animal communities for plant‐frugivore trait matching—the alignment between frugivory‐related plant traits (e.g., fruit size) and frugivore traits (e.g., body mass)—remain unquantified at macroecological scales. Here, we examine how human disturbance and environmental conditions influence trait matching in tropical plant‐frugivore networks. We compiled fruit size data for 1927 plant species from primary sources, along with body mass and dietary information for 1120 frugivorous animal species (birds, mammals and reptiles), and integrated these with 12,708 plant‐frugivore interactions recorded across 102 networks. Using fourth‐corner analyses and structural equation models (SEMs), we quantified how human disturbance and environmental conditions directly and indirectly affected trait matching strength (fruit‐size‐to‐body‐mass correlation) across networks. SEMs revealed that human disturbance weakened trait matching by reducing the range of frugivore body masses within networks, whereas wet and productive environments promoted a higher proportion of fruit in frugivore diets, leading to stronger trait matching. Our results demonstrate that human disturbance weakens plant‐frugivore trait matching through the downsizing of animal communities, thereby providing a quantitative assessment of the decoupling of coevolved relationships between fruiting plants and their animal seed dispersers.

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

A comparative ultrastructural study of pit membranes with plasmodesmata associated thickenings in four angiosperm species - David Rabaey; Frederic Lens; Suzy Huysmans; Erik Smets; Steven Jansen (Protoplasma, 2008)